Deep Learning Activities for Improving Tenth-Grade Students' Reading Performance - Feby Putri Valen Malau; Eva Nurchurifiani; Sri Wahyuningsih (IJLHE: International Journal of Language, Humanities, and Education, 2026)
This study aimed to improve students’ reading performance and learning engagement through deep learning-based activities in English classes. The study employed Classroom Action Research (CAR), which was conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 27 tenth-grade students of SMAS Taman Siswa Teluk Betung in the 2025/2026 academic year. Data were collected through reading tests and classroom observations. The results showed positive changes across the two cycles. In Cycle 1, 6 students (22%) achieved the Minimum Completeness Criteria (MCC), while 21 students (78%) were below the criterion. The observation results showed that students’ learning activity was categorised as less active. In Cycle 2, the number of students who achieved the MCC increased to 19 students (70%), while 8 students (30%) remained below the criterion, with the students were categorised as active and very active. In other words, the strategy resulted in positive changes in the teaching and learning process, as students showed greater engagement in analysing texts, interpreting information, and connecting reading materials to real-life contexts.